Kelp (Saccharina latissima) Mitigates Coastal Ocean Acidification and Increases the Growth of North Atlantic Bivalves in Lab Experiments and on an Oyster Farm - Young, Craig S.; Sylvers, Laine H.; Tomasetti, Stephen J.; Lundstrom, Andrew; Schenone, Craig; Doall, Michael H.; Gobler, Christopher J. (Frontiers in Marine Science, 2022)
Coastal zones can be focal points of acidification where the influx of atmospheric CO2 can be compounded by additional sources of acidity that may collectively impair calcifying organisms. While the photosynthetic action of macrophytes may buffer against coastal ocean acidification, such activity has not been well-studied, particularly among aquacultured seaweeds. Here, we report on field and laboratory experiments performed with North Atlantic populations of juvenile hard clams (Mercenaria mercenaria), eastern oysters (Crassostrea virginica), and blue mussels (Mytilus edulis) grown with and without increased CO2 and with and without North Atlantic kelp (Saccharina latissima) over a range of aquaculture densities (0.3 – 2 g L-1). In all laboratory experiments, exposure to elevated pCO2 (>1,800 µatm) resulted in significantly reduced shell- and/or tissue-based growth rates of bivalves relative to control conditions. This impairment was fully mitigated when bivalves were exposed to the same acidification source but also co-cultured with kelp. Saturation states of aragonite were transformed from undersaturated to saturated in the acidification treatments with kelp present, while the acidification treatments remained undersaturated. In a field experiment, oysters grown near aquacultured kelp were exposed to higher pH waters and experienced significantly faster shell and tissue based growth rates compared to individuals grown at sites away from kelp. Collectively, these results suggest that photosynthesis by S. latissima grown at densities associated with aquaculture increased pH and decreased pCO2, fostering a carbonate chemistry regime that maximized the growth of juvenile bivalves. As S. latissima has been shown to benefit from increased CO2, growing bivalves and kelp together under current or future acidification scenarios may be a synergistically beneficial integrated, multi-trophic aquaculture approach.